The Economy of Greenland. - Sveistrup, Poul P. (Meddelelser om Grønland, 1967)
Economic problems have during many years been viewed in accordance with the mode of thinking of NEWTON and his followers in the natural sciences. I think this has been very useful in many respects, but it should also be possible to learn from the mode of thinking employed by natural science in our century. I have endeavoured to do this in the work on the economy of Greenland which I here present to the reader. The central point is that instead of the idea of the economic man, I have tried to use the idea of the whole man. I hope that this way of thinking will be of interest not only to people interested in the relation between Denmark and Greenland, but also to others who are interested in problems arising where different races meet.